Effect of melatonin on wound healing in normal and pinealectomized rats - Bulbuller, N; Dogru, O; Yekeler, H; Cetinkaya, Z; Ilhan, N; Kirkil, C (Academic Press Inc Elsevier Science, 2005)
Melatonin usage is increasing gradually, but reports of its effects on wound healing are inconsistent. It has been shown that the hormone is synthesized in and secreted from the gastrointestinal system independently of the pineal gland. We have investigated, by means of a comparative study on the healing of incision and anastomotic wounds, whether melatonin has an effect on wound healing independent of the pineal gland. Rats were divided in five groups (n = 10), all of which were subjected to small intestine anastomosis. The first group (control) was otherwise untreated. Exogenous melatonin was given to the rats in second group. The calvaria was opened then closed in the third group (sham operated), whereas the fourth group was pinealectomized and the fifth group were pinealectomized and then treated with melatonin. After anastomosis bursting pressures and incision wound breaking strength were measured on the 7th postoperative day, tissue hydroxyproline levels were determined, and histopathological investigation was performed. It was found that while collagen deposition and epithelization increased concurrently in incision wounds after pinealectomy, only collagen deposition increased at the anastomosis line. Exogenous melatonin decreased collagen synthesis and epithelium proliferation and had negative effects on wound healing in both normal and pinealectomized rats. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: melatonin; pineal gland; pinealectomy; wound healing; anastomosis